Analisis Tindak Tutur Ilokusi Direktif Ceramah Ustadz Das’ad Latif pada Akun YouTube “Kajian Pragmatik” - Gunawan, Andika; Srimularahmah, Andi; Fitriana, Irna (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
This study aims to describe the forms of directive illocutionary acts used by Ustadz Das’ad Latief in his sermons uploaded on his YouTube account. The research employs a descriptive qualitative approach, with data sourced from transcripts of several sermon videos on the channel. Data were collected through observation and recording techniques, followed by the stages of identification, classification, and interpretation of directive illocutionary acts. The findings reveal five types of directive illocutionary acts in Ustadz Das’ad Latief’s sermons: commanding, requesting, inviting, suggesting, and advising. These speech acts reflect a persuasive religious communication style intended to guide listeners toward positive behavior in accordance with Islamic teachings. Reflectively, this study highlights the communicative value of directive speech acts in fostering effective religious discourse and contributes to the development of pragmatic studies in digital religious communication.